The Transformation of Interest Prohibition: A Comparative Study of Riba (Usury) in Contemporary Financial Systems - Aidid, Muhammad Asri (Mazahibuna: Jurnal Perbandingan Mazhab, 2024)
This study aimed to explore the transformation of the concept of riba (usury) within contemporary financial systems, specifically how Islamic jurisprudence has adapted to modern economic practices. The analysis also aimed to understand the evolving interpretation of riba and its implications for Islamic and global financial markets. A comparative analysis was adopted, integrating qualitative methods such as document analysis and a case study of financial systems. This study examined historical and modern interpretations of riba, with a specific focus on the transition from traditional gold and silver standards to fiat money systems. The results showed that the adaptation of riba in modern financial systems required significant transformation, particularly in response to the transition from commodity-based to fiat money. The analysis identified key trends in how riba was reinterpreted within the context of contemporary financial systems as well as discussed the challenges and solutions proposed by Islamic scholars. Additionally, it contributed to the existing body of knowledge by providing a nuanced analysis of how the prohibition of riba was applied in contemporary financial systems, connecting historical perspectives with modern practices. The analysis provided new insights into the dynamic relationship between traditional Islamic financial principles and the evolving global financial landscape. It also showed the importance of continuous investigation of riba in the context of contemporary financial systems. This study suggested that ongoing discourse among Islamic financial practitioners and scholars was crucial for developing solutions to support both traditional principles and contemporary financial realities.